When should we thrombolyse patients with pulmonary embolism? A systematic review of the literature. Issue 11 (21st October 2005) - Harris, T; Meek, S
Abstract : The early mortality in pulmonary embolism (PE) is largely predicted by the associated cardiovascular response, with progressive right ventricular failure, hypotension, shock, and circulatory arrest being associated with increasing mortality. Thrombolysis may improve the prognosis of PE associated with these varying degrees of circulatory collapse, but has no place in the treatment of small emboli with no cardiovascular compromise, as it carries a significant risk of haemorrhage. This review sets out to guide the emergency physician in deciding which patients with PE may benefit from thrombolysis.